Human Resource Development in Democratic Kampuchea, 1975-1979. (September 2014) - Procknow, Greg
I deconstruct the body of literature that frames education and learning in Democratic Kampuchea (DK), 1975-1979. This historical analysis posits that new alternative interpretations can arise when viewing learning under Pol Pot's DK through a human resource development (HRD) lens. The paucity of research or the lack of HRD perspectives on genocidal situations is concerning. An HRD focus as this paper demonstrates will reveal insightful information on the whys and hows the Khmer Rouge (KR) learned. Learning designs contrived for Khmer learners connote an employee-work relationship (forced labor); hence, why the need for an HRD interpretation of these learning events. Many DK scholars assert that education under the KR was unorganized, inconsistent, and without planning. My deconstruction of the DK historical record will call these views into question. When reviewing the historical record through an HRD lens, KR educational initiatives made sense within the context of the madness they perpetrated.